Implementasi Metode Drill dalam Program Pendampingan Bahasa Inggris bagi siswa TPQ di Desa Maleo - Akhmad, Zulkifli; Rustam Saleh, Yuwin; Akhmad, Enni (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to implement the drill method in an English teaching assistance program for TPQ (Qur'anic Elementary School) students in Maleo Village, Pohuwato Regency, Gorontalo, utilizing the Asset-Based Community Development (ABCD) approach. The teaching assistance was carried out by students from IAIN Sultan Amai Gorontalo as part of the Thematic Social Work Program (KKS-T). The study followed the four core stages of the ABCD framework: Discovery, Dream, Design, and Delivery. The findings indicate that this approach successfully optimized local assets, including the active participation of TPQ teachers, youth organizations, and parents. The drill method was implemented over a 12-day period, focusing on pronunciation, basic vocabulary, and simple conversations, and was enriched with songs and games. Based on the pre-test and post-test results, the students' average scores increased significantly from 5.1 to 70.0. In addition to improving students’ English proficiency, the program also fostered students’ social awareness and contributed to the empowerment of the local community. This study recommends the integration of community asset-based learning models and the drill method as effective strategies for basic English instruction in non-formal educational settings.